INTERVENSI PEMERINTAH DALAM EKONOMI CAMPURAN: PENYEDIAAN PUBLIC GOODS DAN PENGATURAN PRIVATE GOODS DI SEKTOR KESEHATAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: The best way to run the economy is usually to let people produce and consume goods without restrictions or government intervention. This interaction of supply and demand in the market leads to an equilibrium at the point where marginal benefits equal marginal costs. The power of market prices arising from this perfect competition organizes production and consumption in a way that maximizes welfare, so-called as Pareto-optimality.Yet, conditions are not always "perfect".There are things that only government can do. This paper discusses the presence of public goods in the health sector as an example where market fails to perform efficiently. Subject and methods: This policy paper reviews micro-economic theories that address public goods and private goods in the health sector. Empirical evidence is presented to support (or to refute) the theories. Results: A pure public good is a good or service, such as information that warns the hazard of tobacco use, but the consumption of which by one person does not reduce its availability to others in society. It is not possible to charge for a public good because no one can be excluded from using them, and no one wants to charge for because it does not cost anything to accommodate additional users. As such the public good must be subsidized or provided by government if it is to be produced efficiently. The government production of a public good also is advantageous because government can assess taxes to pay for it. Conclusions: This paper has discussed the policy issues concerning the provision of public goods and regulation of private goods by the government. Firstly, the definitions of public good and private good were explained, by citing relevant examples in the health sector. The efficient level of provision of a public good, market failure due to public goods, the rationale for government intervention, and privatization of public goods, were then discussed along the remaining of the paper.